De co-ordenador a coordenador pedagógico: vivências e percepções no cotidiano do trabalho - Araujo, Vanderleia Schlickmann de (2023)
The legal recognition of child education as the first stage of basic education by the Law of Directives and Bases of National Education (LDB nº 9394/96) (BRASIL, 1996) brought the same requirements for early childhood care institutions as for other educational institutions. The demand for new tasks for professionals has led to the need for other functions in addition to the Pedagogical Coordinator. Since then, cities have reorganized their school systems to comply with federal legislation. In the city of Francisco Beltrão in the state of Paraná, the function of Pedagogical Coordinator was introduced in 2019 at the Center for Children's Education (CEC). We justify the need for this study with the search for data to understand how the process took place, the progress and limitations of Pedagogical Coordination, with the aim of identifying possible contributions to strengthen and consolidate the work to coordinate the educational service of babies and very young children (from zero to three years and 11 months old). Our general research objective is to identify the understanding of the pedagogical coordinators of the children's education centers in Francisco Beltrão/PR about their function and performance in said institutions. Our specific objectives were organized to investigate the historical and epistemological context of the function of pedagogical coordination based on the productions in the region; the function of pedagogical coordination in children's education considering the Brazilian, the state and the city’s legislation; To map the Pedagogical Coordination staff in the CECs of Francisco Beltrão/PR through data collection by questionnaires with the aim of identifying the specificities, gaps and understanding of these people in their work. Almeida; Placco and Souza (2011; 2013. 2015; 2021), Barbosa (2009); Campos (2002); Kramer (2006; 2006); Pimenta (1995); Waltrick (2008); Libâneo (2001; 2010); Conceição (2014); Franco (2008; 2016); Oliveira (2013), among others theoretically support this research. We used the qualitative-quantitative approach as a methodology and the bibliographical and documentary study of the Pedagogical Coordinator's function as a research tool, in addition to data collection through questionnaires sent to the other coordinators of the 20 municipal CECs.The data analyzes were made based on the data triangulation (TRIVIÑOS, 2008; ZAPELLINI; FEUERSCHÜTTE, 2015) and in the phenomenological paradigm (BICUDO; CAPPELLETTI, 1999; MERLEAU-PONTY, 2011). The results point to the relevance of the work of pedagogical coordination in the movement of reflection-action and improvement of theoretical-methodological teaching practice. Most coordinators reported knowing and understanding their functions and tasks, but the lack of functional regulation, the challenges and the working conditions they reported lead to an excess of tasks and high turnover, making it difficult for these professionals to construct their identities. Thus, we highlight, the necessary implementation of concrete public policies for the recognition and appreciation of Early Childhood Education and its professionals in the context investigate.